The Role of Curcumin in Oral Health and Diseases: A Systematic Review - Francesco Inchingolo; Alessio Danilo Inchingolo; Giulia Latini; Irma Trilli; Laura Ferrante; Paola Nardelli; Giuseppina Malcangi; Angelo Michele Inchingolo; Antonio Mancini; Andrea Palermo; Gianna Dipalma (MDPI AG, 2024)
Curcumin (Curcumin) belongs to the polyphenol family. It is extracted by drying the root of a plant of Asian origin, belonging to the Zingiberaceae family. The best-known species is Curcumincuma Longa. Curcumin has been recognized as having great therapeutic powers since ancient times. Studies on curcumin have since confirmed its powerful antioxidant properties, preventing both the formation of free radicals and their neutralization, having anti-inflammatory, antibacterial, immunological, and neuroprotective properties, as well as being a regulator of the intestinal microbiota with beneficial effects on the clinical manifestations of metabolic syndrome. Our study aimed to highlight how all these therapeutic aspects could benefit oral health, both preventing and improving the course of pathological processes. The effect of mouthwashes, and curcumin-based gels on the regulation of bacterial plaque and in the control of gingivitis, was largely comparable to that of using 0.20% chlorhexidine, with fewer side effects. Being a highly hydrophobic substance, it has a high permeability to cross the cell membrane. Bioavailability increases when combined with liposoluble substances (e.g., olive oil) and piperine, which improves absorption. Curcumin also has a negligible degree of toxicity, making it an excellent alternative to the use of gold standard products for oral disinfection.